2016
DOI: 10.3390/inorganics4040034
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Reduction of Phosphine Oxides Using Polymethylhydrosiloxane

Abstract: Abstract:A simple protocol is presented here for the use of inexpensive polymethylhydrosiloxane (PMHS), a waste product of the silicon industry, as stoichiometric reducing agent for phosphine oxides to phosphines, a highly desirable reaction to recover P-based ligands from their spent form. The reactions were studied by screening parameters, such as substrate to reductant ratio, temperature and reaction time, achieving good conversions and selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Catalyst activity could thus be renewed through the addition of disiloxane reducing agents 36,[39][40][41][42] used to regenerate the phosphine. Indeed, we found that addition of 1,3-diphenyldisiloxane (DPDS) to our PO/B1/P1/CO 2 reaction mixture allowed for >99% conversion of PO (Fig.…”
Section: Screening Of La/lb Copolymer Catalystsmentioning
confidence: 99%
“…Catalyst activity could thus be renewed through the addition of disiloxane reducing agents 36,[39][40][41][42] used to regenerate the phosphine. Indeed, we found that addition of 1,3-diphenyldisiloxane (DPDS) to our PO/B1/P1/CO 2 reaction mixture allowed for >99% conversion of PO (Fig.…”
Section: Screening Of La/lb Copolymer Catalystsmentioning
confidence: 99%
“… 15 17 These precursors tolerate the reaction conditions necessary to construct more complex architectures 18 although the protection must be removed in the penultimate 12 , 19 or final 20 , 21 step of the ligand synthesis. Thus, much attention has been focused on the conversion of P (V) =O to P (III) 15 , 16 ( Scheme 1 a), including the use of silanes and siloxanes such as HSiCl 3 , 22 25 HSiCl 3 /Ph 3 P, 26 Si 2 Cl 6 , 24 , 27 Si 2 Me 6 with CsF/TBAF, 28 HSi(OEt) 3 /Ti(O- i -Pr) 4 , 29 PhSiH 3 , 30 32 1,1,3,3-tetramethyldisiloxane (TMDS) with CuX 2 , 33 polymethylhydrosiloxane (PMHS), 34 , 35 1,3-diphenyldisiloxane (DPDS), 36 and (EtO) 2 MeSiH/(RO) 2 P(O)OH; 37 aluminum hydrides such as LiAlH 4 , 38 , 39 LiAlH 4 /CeCl 3 , 40 AlH 3 , 41 and HAl( i -Bu) 2 ; 42 low-valent metals such as SmI 2 /HMPA (hexamethylphosphoramide) 43 or Cp 2 TiCl 2 /Mg; 44 hydrocarbon/activated carbon; 45 and electrochemical reduction. 46 48 A mild iodine-catalyzed reduction of phosphine(V) oxides employing a sacrificial electron-rich phosphine was developed by Laven and Kullberg, 49 while Li et al 50 employed less expensive phosphite, although in both cases P (V) =O-containing contaminants must be removed from the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significance of phosphine­(III) compounds, a variety of anaerobic syntheses have been reported. , However, the sensitivity of phosphine­(III) to oxidation (requiring only minutes to hours) has led to the widespread use of “protected” phosphines, such as phosphine–borane adducts , and phosphine­(V) sulfides , but predominantly phosphine­(V) oxides. These precursors tolerate the reaction conditions necessary to construct more complex architectures although the protection must be removed in the penultimate , or final , step of the ligand synthesis. Thus, much attention has been focused on the conversion of P (V) O to P (III) , (Scheme a), including the use of silanes and siloxanes such as HSiCl 3 , HSiCl 3 /Ph 3 P, Si 2 Cl 6 , , Si 2 Me 6 with CsF/TBAF, HSi­(OEt) 3 /Ti­(O- i -Pr) 4 , PhSiH 3 , 1,1,3,3-tetramethyl­disiloxane (TMDS) with CuX 2 , polymethyl­hydrosiloxane (PMHS), , 1,3-diphenyl­disiloxane (DPDS), and (EtO) 2 MeSiH/(RO) 2 P­(O)­OH; aluminum hydrides such as LiAlH 4 , , LiAlH 4 /CeCl 3 , AlH 3 , and HAl­( i -Bu) 2 ; low-valent metals such as SmI 2 /HMPA (hexamethyl­phosphoramide) or Cp 2 TiCl 2 /Mg; hydrocarbon/activated carbon; and electrochemical reduction. A mild iodine-catalyzed reduction of phosphine­(V) oxides employing a sacrificial electron-rich phosphine was developed by Laven and Kullberg, while Li et al employed less expensive phosphite, although in both cases P (V) O-containing contaminants must be removed from the final products. Thus, disadvantages of these procedures include harsh reaction conditions, toxic and/or highly reactive, potentially explosive reducing agents, narrow scope or undesirable side reactions, e.g.…”
Section: Introductionmentioning
confidence: 99%